2017
DOI: 10.13181/mji.v26i1.1494
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasound joint outcomes in severe hemophilia A children receiving episodic treatment in Indonesian National Hemophilia Treatment Center

Abstract: Background: Recurrent joint bleeds leading to arthropathy is the main problem in severe hemophilia children. This study aimed to investigate joint status in severe hemophilia A children receiving episodic treatment in Cipto Mangunkusumo Hospital, Jakarta.Methods: A cross-sectional study was conducted in Cipto Mangunkusumo Hospital as Indonesian National Hemophilia Treatment Center on children (4–18 years) with severe hemophilia A, who previously received episodic treatment, with no history of inhibitor factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
2
Order By: Relevance
“…In the current study, the mean HJHS was 16.8 ± 12.8. We found a nonstatistically association between HJHS and the presentation age; opposite to this finding, an Indonesian study by Sari et al 17 observed that children with severe hemophilia who were receiving episodic treatment evaluated by HJHS and HEAD-US scoring show more severe joint damage in older children. In the present study, when the HJHS was plotted against the age of the patients, we found a nonstatistically significant linear correlation between them.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the current study, the mean HJHS was 16.8 ± 12.8. We found a nonstatistically association between HJHS and the presentation age; opposite to this finding, an Indonesian study by Sari et al 17 observed that children with severe hemophilia who were receiving episodic treatment evaluated by HJHS and HEAD-US scoring show more severe joint damage in older children. In the present study, when the HJHS was plotted against the age of the patients, we found a nonstatistically significant linear correlation between them.…”
Section: Discussioncontrasting
confidence: 99%
“…Ghany et al 9 also reported a nonstatistically significant correlation between FISH and age. Those findings are opposite to the reported in a similar study where FISH had a good connection with the age of patients with severe ( r =−0.63, P =0.01) and moderate hemophilia ( r =−0.55, P =0.02) 17 . We found that by increasing the number of affected joints, the lower the FISH score; the FISH score was significantly negatively correlated with the number of affected joints ( r =−0.352, P =0.012).…”
Section: Discussioncontrasting
confidence: 99%
“…Repeated joint bleeding in haemophilia often leads to joint deformity and dysfunction, which seriously affects the quality of life of patients ( 9 ), and with age, these lesions become more apparent ( 10 ). US has recently attracted growing interest as a potential tool to assess joint status and identify early arthropathic changes in haemophilia patients, which can ensure initiation of treatment as soon as possible and thereby prevent joint damage ( 11 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, this study was conducted on hemophilia patients who had received prophylaxis treatment. In Indonesia, most hemophiliac patients receive episodic treatment, due to financial challenges and unavailability of prophylaxis treatment [ 14 , 15 ]. Therefore, many pediatric hemophiliac patients have moderate to severe joint problems.…”
Section: Introductionmentioning
confidence: 99%